Local defect formation in short glass fibre reinforced polymers – micro-mechanical simulations and interrupted in-situ experiments - Julia Maurer; Denise Krölling; Dietmar Salaberger; Michael Jerabek; Johann Kastner; Zoltán Major (Acta Polytechnica CTU Proceedings)
Discontinuous fibre reinforced polymers are widely used in various industry sectors and often replace conventional materials, due to lower production costs and their lightweight structure. For improvement of the component design, detailed knowledge of the failure mechanisms are necessary. To better understand the defect formation and thus the micro-mechanics, the strain behaviour in single fibres was analysed by micro-mechanical simulations of Representative Volume Elements (RVE). Therefore, selected fibres – similar orientated as in the real structure – were chosen for detailed analysis. Additionally, the defect formation next to selected fibres was investigated by X-ray computed tomography (CT). Furthermore, the critical fibre length was estimated based on the protruding fibre length of the fracture surface. Overall the simulation results correspond to theory. However, the detailed local inspection of the experimental volume data showed a rather strong influence of neighbouring fibres.